The Small Matter of Suing Chevron - Sawyer, Suzana (Duke University Press, 2022)
Suzana Sawyer traces Ecuador's lawsuit against the Chevron corporation for the environmental devastation resulting from its oil drilling practices, showing how distinct legal truths were relationally composed of, with, and through crude oil.